Metodología para la implementación de un Sistema de Gestión de Energía en el Edificio de Unidades Productivas del Campus San Cayetano de la UTPL, apoyado en la norma INEN-ISO 50001:2012 para el cumplimiento de la norma INEN 2506:2009. - Quichimbo Montalván, Bruno Gonzalo (2014)
In this paper the authors developed a methodology and procedural framework for easy application, to verify compliance with the standard INEN 2506:09, and aimed at the implementation of INEN ISO 50001: 2012. The methodologies and procedures developed are applied demonstratively in the building called EUP Campus San Cayetano at the UTPL, demonstrating the low compliance with the standard. Finally, a plan for improvements in energy management EUP is proposed by authors